Angström-Prescott empirical model to estimate solar radiation in Norte de Santander, Colombia - Contreras-Sepúlveda, Wilmer; Galban-Pineda, Migan Giuseppe; Bustos-Márquez, Luis Fernando; Sepúlveda-Mora, Sergio Basilio; Ramírez-Mateus, Jhon Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The document shows the application of the empirical Angström-Prescott model in different places in Norte de Santander, Colombia. The model estimates solar radiation from hours of sunlight, at a site where brightness and solar radiation are measured. The data were obtained from the Institute of Hydrology, Meteorology and Environmental Studies, IDEAM; algorithms were developed in RStudio to process and analyze the information. The model establishes a linear relationship between solar radiation and the hours of sunlight, in a specific geographic location. Therefore, regression analyzes were performed for three different sites, using historical records of brightness and solar radiation, obtaining the R-squared coefficients of: 0.73, 0.78, and 0.42. The models were then extrapolated to nearby regions with solar brightness records, but without solar radiation data, to obtain an estimate of radiation at these locations. Finally, a database was created with monthly average information on solar radiation for various subregions of Norte de Santander, which can be used for the design and implementation of photovoltaic systems.